THE ROLE OF THE ENVIRONMENT IN FITRAH EDUCATION - ANSORI, MUHAMAD ANSORI (TAWASUT, 2023)
In the world of education, the environment is an important component and has a major influence on students. It is mentioned in the Qur'an and Hadith that the environment can also affect the basic human nature which then develops into an object of education in education. Islamic education has a goal to develop the potential of this nature so that happiness is achieved in this world and the hereafter. Namely the creation of a person who is pious, has noble character and has life skills according to his talents and interests. Children born in a good environment such as boarding schools are certainly different from children born in prostitution and so on. So that educators in such an unfavorable environment must be more active in educating their aqidah and morals. in contrast to educators in the pesantren environment, of course they have another focus. Therefore, it is necessary to conduct more in-depth research on how important the role of the environment in nature education is.